Leadership handbooks of practical theology ; v. 2 - Berkley, James D., 1950- (Grand Rapids, MI Baker, 1994)
Contents v. 2 : Outreach and care. Includes bibliographical references.
Reprints entitled : Leadership handbook of outreach and care. Series name changed to : Leadership handbooks
Keywords: Theology, practical -- handbooks, manuals, etc